2012
DOI: 10.1007/s13353-012-0127-8
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of developing rye grain with contrasting resistance to preharvest sprouting

Abstract: Significant differences in the two-dimensional electrophoresis patterns of proteins from developing rye grain were found to be associated with resistance and susceptibility to preharvest sprouting (PHS). Mass spectrometry of individual spots showing different abundance in PHS-resistant and PHS-susceptible lines identified proteins involved in: reaction to biotic and abiotic stresses, including oxidative stress, energy metabolism and regulation of gene expression. Highly differentiated abundance of proteins fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The present experiment however did not identify the QTL for PHS on chromosomes 3RS, 6RL, and 7RS detected earlier by using both QTL mapping and BSG analysis. A proteomic analysis of lines representing the resistant and susceptible lines of the 541 × Ot1-3 cross showed that many identified proteins represented defensive functions against microbial and insect pests [ 28 , 29 ]. This should not be surprising as only the intact grain surface without any destructive effects of pets’ activities can resist water infiltration, which directly induces sprouting and the α-amylase production.…”
Section: Discussionmentioning
confidence: 99%
“…The present experiment however did not identify the QTL for PHS on chromosomes 3RS, 6RL, and 7RS detected earlier by using both QTL mapping and BSG analysis. A proteomic analysis of lines representing the resistant and susceptible lines of the 541 × Ot1-3 cross showed that many identified proteins represented defensive functions against microbial and insect pests [ 28 , 29 ]. This should not be surprising as only the intact grain surface without any destructive effects of pets’ activities can resist water infiltration, which directly induces sprouting and the α-amylase production.…”
Section: Discussionmentioning
confidence: 99%
“…The proteomic protocol used, including 2-DE and MS to identify differentially accumulated kernel proteins between the RL and SL of wheat, was the same as that described in detail by Masojć and Kosmala [31] and Masojć et al [32] . Protein extraction was performed according to the method of Hurkman and Tanaka [33] using 0.7 M sucrose, 0.5 M TRIS, 30 mM HCl, 50 mM EDTA, 2% DTT, and 0.1 M KCl as components of the extraction buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Protein accumulation profiles of three enzymes of the Calvin cycle (pFBA, pPGK, pGAPDH) and seven antioxidant enzymes including glutathione reductase (GR, AS06 181), chloroplastic glutathione peroxidase (GPX, AS04 055), chloroplastic Fe-dependent superoxide dismutase (Fe-SOD, AS06 125), chloroplastic Cu/Zn superoxide dismutase (Cu/Zn-SOD, AS06 170), manganese superoxide dismutase (Mn-SOD, AS09 524), L-ascorbate peroxidase (APX, AS08 368) and catalase (CAT, AS09 501), were analyzed. Total proteins were extracted from pooled leaves using Hurkman and Tanaka protocol with slight modifications [4,62,63]. Briefly, 200 mg of powdered tissue was homogenized with 500 µL of extraction buffer (0.7 M sucrose, 0.5 M TRIS, 30 mM HCl, 50 mM EDTA, 2% DTT, and 0.1 M KCl).…”
Section: Protein Accumulation Of the Calvin Cycle And Antioxidant Enz...mentioning
confidence: 99%